A Queueing Network Model for Performance Analysis of Single-Radio and Dual-Radio 802.11 Wireless Mesh Networks - Kaddour, Mejdi (INFOCOMP Journal of Computer Science, 2011)
Wireless mesh networks address the growing requirements for networks that are highly scalable and cost-effective, offering end-users large access areas beyond traditional WLAN boundaries, and provide a viable alternative when wired backhaul cannot be supported or afforded. The success of these networks depends on the availability of accurate models and tools for assessing their performances at each layer. However, to date, most analysis of wireless networks has been focused on single-hop and ad hoc multi-hop networks under saturated conditions. In this paper, we introduce an analytical model specifically designed to the performance evaluation of 802.11-based wireless mesh networks under finite load. This model relies on Markov chains for evaluating packet service delays of mesh clients and mesh routers that operate with 802.11 DCF, and open G/G/1 queueing networks for deriving explicit expressions of average end-to-end delay on single-radio and dual-radio WMNs. Our analytical results are verified through extensive simulations. The results quantify the impact of the dedicated backhaul channel and the strong dependency between end-to-end delay and radio range. Keywords: WMN, 802.11 DCF, end-to-end delay, Markov model, queueing network, diffusion